2007
DOI: 10.1097/01.tp.0000250598.29377.13
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of Human Anterior Cruciate Ligaments with Pig Ligaments: A Model for Anti-Non-Gal Antibody Response in Long-Term Xenotransplantation

Abstract: These antibodies contribute to a low-level inflammatory process that aids in gradual xenograft replacement by infiltrating host fibroblasts that align with the pig collagen "scaffold" and secrete collagen matrix. The assays monitoring anti-non-gal antibodies will help to determine whether long-term survival of live organ xenografts requires complete suppression of this antibody response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
151
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(156 citation statements)
references
References 32 publications
5
151
0
Order By: Relevance
“…For these reasons, the use of xenografts took off, with numerous products currently available [307,308]. Although positive functional scores and improved movement as early as 6 months post-operation have been reported [309], many studies have demonstrated high failure rates and tearing incidents [310][311][312][313], which may be attributed to processing conditions (e.g. decellularisation, cross-linking, sterilisation) employed to battle immune rejection, which remains the major obstacle for both allogeneic [314,315] and xenogeneic [316] approaches.…”
Section: Tissue Grafts -The Top-down Approach For Tendon Repairmentioning
confidence: 99%
“…For these reasons, the use of xenografts took off, with numerous products currently available [307,308]. Although positive functional scores and improved movement as early as 6 months post-operation have been reported [309], many studies have demonstrated high failure rates and tearing incidents [310][311][312][313], which may be attributed to processing conditions (e.g. decellularisation, cross-linking, sterilisation) employed to battle immune rejection, which remains the major obstacle for both allogeneic [314,315] and xenogeneic [316] approaches.…”
Section: Tissue Grafts -The Top-down Approach For Tendon Repairmentioning
confidence: 99%
“…Anti-non gal IgG Ab activity in the pig ligament recipients increased on average by 5-10 folds in comparison with pre-implantation serum in each of the patients (Stone et al, 2007). This increase is much lower than the ~100 fold increase in anti-Gal Ab activity observed in the patient receiving intraperitoneal infusion of mouse fibroblasts.…”
Section: Anti-non Gal Ab Response In Recipients Of Pig Ligamentmentioning
confidence: 56%
“…For such analysis, anti-Gal Abs have to be removed from the tested human sera prior to the assay. This anti-Gal depletion is feasible by adsorption of anti-Gal Ab on rabbit RBC or on glutaraldehyde rabbit RBC (Galili et al, 2001;Stone et al, 2007) since these RBC present the highest number of -gal epitopes among mammalian RBC (Ogawa & Galili, 2006). As described below, studies on anti-non gal Abs in xenograft recipients have indicated that their production is very different from that of elicited anti-Gal Abs.…”
Section: Most Of the Proteins Within Pig Xenografts Are Expected To Bmentioning
confidence: 99%
See 2 more Smart Citations